To små teatre - Ejgod Hansen, Louise (Peripeti, 2009)
The article examines how cultural policy promotes and restricts different forms of theatre organization. Three types of theatre organizations, the institution, the group and the project, are used to analyze the relationship between organization and artistic production. The object of the analysis is the local theatre system in Denmark in general and the cases of Randers EgnsTeater and Holbæk Teater in particular.